Elementos de manutenção de transformadores de potência - Fonseca, Jackson Farias [UNESP] (2014)
The intended purpose of this paper is to present the main commissioning tests for power transformers and the most used techniques in industrial segment, it is also discussed your results and consequences in the equipment’s normal operation. Also in this text, it is given specific information concerning a maintenance plan compatible to power transformers, with elements of preventive and predictive maintenance, exposing essential components, tests and the regulations current, showing how analyze and interpreted the results from this maintenance resources. Also in this paper is submitted the economic impact of damage to transformers and how the correct maintenance method can minimize them. The objective of this text is demonstrate the importance of the equipment and the benefits of proper maintenance, much of in financial terms as in electric system reliability